No cover image available Antioxidant and hepatoprotective effects of flagellaria indica, lygodium microphyllum and synedrella nodiflora against carbon tetrachloride-mediated oxidative hepatic damage in rat - Charles Gnanaraj A/L John Sandanaraj (2016)
Plants of Malaysian origin are well known for their aroma and taste but many are still unaware of the medicinal properties that the plants possess. Synedrella nodiflora (SN), Flagellaria indica (FI) and Lygodium microphyllum (LM) are tropical medicinal plants that are being used by the natives of Sabah as medication for several ailments. This study was conducted to evaluate the antioxidant capacity of the selected herbal plants and their hepatoprotective effects against carbon tetrachloride (CCl4)-mediated oxidative hepatic injury in rats. Several in-vitro studies were carried out on SN, FI and LM to determine their antioxidative potential. Crude aqueous extract was subjected to gas chromatography and mass spectrometry (GC-MS) analysis. The obtained data from total phenolic and flavonoid contents revealed that these plants possessed strong antioxidant activities and have the ability to scavenge DPPH free radicals effectively. The GC-MS analysis of these plants demonstrated the presence of different bioactive compounds of various natures. The identified bioactive compounds have been reported with antioxidant, anti-inflammatory, anti-microbial and hepatoprotective properties. In-vivo studies is based on oral feeding of adult Sprague-Dawley rats with aqueous extracts of SN, FI and LM once daily for fourteen consecutive days at different doses (0 – 600 mg/kg b.w.) prior to CCl4 treatment (1.0 ml/kg b.w.) on the 13th and 14th day to induce liver damage. Biochemical studies showed that aqueous extracts of SN, FI and LM were able to prevent the free radical offshoots of CCl4 from oxidizing the lipid membrane of hepatocytes hence preserving the hepatic antioxidant and related enzymes. CCl4 only treated rat hepatocytes were mostly undergoing apoptosis due to structural damage of hepatic organelles. Hepatic nuclei and other cytoplasmic organelles were protected by SN, FI and LM as evidenced by electron microscopic studies. Immunohistochemical studies revealed that the administration of plant extracts decreased the expression of oxidative stress markers 4-hydroxyl-2- nonenal (HNE) modified protein adducts and 8-hydroxy-2-deoxygunosine (8-OHdG) as compared to the CCl4-intoxicated group. Furthermore, the over-expression of proinflammatory cytokines markers tumor necrosis factor-alpha, interleukin-6 and prostaglandin E2 are also reduced. Histopathological (H & E) alterations exhibited the protective effects of SN, FI and LM against CCl4 mediated hepatic injury. Collectively, these plants alleviated CCl4-induced hepatic damage via modulation of hepatic metabolizing enzymes, suppression of oxidative stress, inhibition of inflammatory cytokines and PGE2 in liver. These findings exhibit the potential prospects of SN, FI and LM as functional ingredients to prevent ROS-related liver damage. Therefore, it can be concluded that the hepatoprotective effects of selected herbal plants might be ascribable to its antioxidant and free radical scavenging property.